QUALITY TEST OF THE NARCOTICS EVIDENCE DETECTION SYSTEM AT THE PROSECUTOR'S OFFICE OF THE REPUBLIC OF INDONESIA WITH ISO 25010 - Agit Muhammad; Tukhas Shilul Imaroh (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to test the quality by implementing ISO 25010 on the Narcotics Detection System of the Republic of Indonesia Prosecutor's Office. This research method uses a descriptive quantitative method. The population of this study consisted of 100 employees spread throughout the High Prosecutor's Office in Indonesia. The sampling technique used was overall sampling. The research data was conducted by providing an online questionnaire. Supporting data was also obtained from the results of blackbox testing. The analysis method was carried out by finding the percentage of data against the classification of data that had been created. The results of the study can show: 1) Users are satisfied with the Narcotics Detection System that has been tested, 2) The quality of the Narcotics Evidence Detection System is in accordance with ISO 25010 Functional Suitability which contains sub-characteristics of Functional Completeness, Functional Correctness, and Functional Appropriateness. The contribution of this research is expected so that the development of this Narcotics Evidence Detection System can be better in its implementation, so that employees who use it can be better assisted and also the data obtained from the system becomes more accurate